Role of Functional Literacy and its Impact on Women’s Empowerment (Journal of Social Sciences Review, 2023)
This research paper aims to elucidate the synergistic outcomes resulting from the integration of functional literacy initiatives with the objective of promoting women's empowerment in the District of Mardan. The research adopts a quantitative approach, with the primary objective of investigating the influence of functional literacy on women's empowerment and exploring its direct effects. The population of the study consisted of all five hundred female individuals enrolled in the functional literacy program in District Mardan. Hundred females were conveniently chosen from two union councils as a sample. In order to examine the data, descriptive statistics i.e. average and variability measured by the standard deviation were utilized. The results were tabulated along with corresponding interpretations. The primary outcome of the study indicated that knowledge of functional literacy positively influenced the lives of participants. Moreover, the research findings emphasized the crucial contribution of organizations in promoting women's empowerment through the facilitation of functional literacy. In order to build upon these discoveries, it is advised that future investigations delve into the incorporation of novel and advancing technologies like artificial intelligence and virtual reality within functional literacy initiatives. This exploration holds the potential for amplifying the influence of such programs on women's empowerment.
Keywords: Functional Literacy; Women Empowerment; Females; Mardan District